2008
DOI: 10.1111/j.1365-2648.2007.04492.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of personality and self‐efficacy in the selection and retention of successful nursing students: a longitudinal study

Abstract: More research is needed to explore the attributes of successful nursing students and the potential contribution of psychological profiling to a more effective selection process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(130 citation statements)
references
References 56 publications
3
125
0
1
Order By: Relevance
“…It revealed that self-esteem was associated with major satisfaction, irrespective of gender (males, β=0.30, females, β=0.23). This agrees with previous research [11,12] that showed positive self-image was a prerequisite of adjustment or attrition. Based on related research on Big-Five personality factors [36][37][38], we assumed that major satisfaction of nursing students would be associated with conscientiousness and extraversion.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It revealed that self-esteem was associated with major satisfaction, irrespective of gender (males, β=0.30, females, β=0.23). This agrees with previous research [11,12] that showed positive self-image was a prerequisite of adjustment or attrition. Based on related research on Big-Five personality factors [36][37][38], we assumed that major satisfaction of nursing students would be associated with conscientiousness and extraversion.…”
Section: Discussionsupporting
confidence: 82%
“…We selected predictors associated with major satisfaction based on previous studies and these predictors fall into three categories. First, the personal characteristics of individuals played a key role in attrition of nursing students [11,12]. Based on previous research, to represent personal characteristics, we selected openness, conscientiousness, extraversion, agreeableness, neuroticism [13], and self-esteem [14].…”
Section: Introductionmentioning
confidence: 99%
“…Both these studies used general self-efficacy scales. McLaughlin et al (2007) found that in a study of 384 nursing students, high self-efficacy (from an occupational perspective) was related to higher academic achievement; and Usher and Pajares (2006) established that academic achievement was related to self-efficacy in 468 pupils of varying ethnicity. Overall researchers have tended to support Bandura's theory that self-efficacy is positively related to an individual's achievement.…”
Section: Self-efficacymentioning
confidence: 99%
“…Despite this impetus for predicting (8), in Iran the applicants' personality characteristics are not assessed before admittance to nursing educational program (12). The consequence is that about half of nurse students admitted to nursing programs possess personality types incompatible with the nursing profession (18).…”
Section: B a Ck Grou Ndmentioning
confidence: 99%